The impact of an experimental nutritional intervention in childhood on education among Guatemalan adults - Maluccio, John; Hoddinott, John F.; Behrman, Jere R.; Martorell, Reynaldo; Quisumbing, Agnes R.; Stein, Aryeh D. (International Food Policy Research Institute, 2006)
Studies have shown that malnourished children in developing countries score lower on tests of cognitive function and fail to acquire fine motor skills at the normal rate. Do the effects of nourishment—good or bad—in early childhood linger into adolescence and adulthood, or do they fade away after a few years? This paper provides new evidence of the effects of early childhood nutritional interventions on adult outcomes, using longitudinal data and methods well suited to address the concerns that have been raised about earlier studies.